Odpowiedzi

Najlepsza Odpowiedź!
2010-02-05T13:58:27+01:00
A)8x+5=7x
8x-7x=-5
x=-5
spr. 8*(-5)+5=7*(-5)
-35=-35 tak

b)7n+2=6n-3
7n-6n=-5
n=-5
spr. -35+2=-30-3
-33=-33 tak
c)-x+25=2x-2
-3x=-27/:(_3)
x=9
spr.16= 16 tak
d)-9z-7=-z-6
-8z= 1/:(-8)
x=-1/8
spr. 9/8-7=1/8-6
47/8= 47/8 tak
e)25m-3=24m-4
m= -1
spr. -25-3=-24-4
-28=-28 tak
f)-s+15=4s-14
-5s=-29/(-5)
s=29/5
spr.46/5= 46/5 tak
g)17y+28=19y+27
-2y=-1/(-2)
y=1/2
spr. 17/2+28=19/2+27

h)8k-19=-8k+19
60 3 60
2010-02-05T18:50:28+01:00
A)8x+5=7x
8x-7x= -5
x= -5

sprawdzenie
8x+5=7x
8*(-5)+5 = 7*(-5)
-40+5 = -35
-35 = -35

b)7n+2=6n-3
7n-6n = -3-2
n = -5

sprawdzenie
7n+2=6n-3
7*(-5)+2 = 6* (-5) -3
-35+2 = -30 -3
-33 = -33

c)-x+25=2x-2
-x-2x = -2 - 25
-3x = -27 / (-3)
x = 9

sprawdzenie
-x+25=2x-2
-9+25 = 2*9 - 2
16 = 18-2
16 = 16

d)-9z-7=-z-6
-9z+z = -6+7
-8z = 1 / (-8)
z= -¹/₈

sprawdzenie
-9z-7=-z-6
-9 * (-¹/₈) -7 = - (-¹/₈) -6
⁹/₈ - 7 = ¹/₈ - 6
-5⁷/₈ = -5⁷/₈

e)25m-3=24m-4
25m-24m = -4+3
m= -1

sprawdzenie
25m-3=24m-4
25*(-1) -3 = 24* (-1) -4
-25-3 = -24-4
-28 = -28

f)-s+15=4s-14
-s-4s=-14-15
-5s = -29 / (-5)
s = 5,8

sprawdzenie
-s+15=4s-14
-5,8 +15 = 4*5,8 -14
9,2 = 23,2 -14
9,2 = 9,2

g)17y+28=19y+27
17y-19y= 27-28
-2y = -1 /(-2)
y = ½

sprawdzenie
17y+28=19y+27
17* (½)+28 = 19 *(½) + 27
8,5 +28 = 9,5 + 27
36,5 = 36,5

h)8k-19=-8k+19
8k+8k = 19 + 19
16k = 38 / 16
k= 2³/₈

sprawdzenie
8k-19=-8k+19
8*2³/₈ -19 = -8 *2³/₈ +19
19-19 = -19+19
0=0
70 4 70